Hemihepatectomy and Replacement of The Afferent Hepatic Blood Supply in The Dog. Issue 2 (1989) - Boerma, Egge J.; de Boer, Herman H. M.; van der Heyde, M. Niels; van Haelst, Urbain J. G. M.
Abstract : Hemihepatectomy along with portal vein or hepatic artery replacement in dogs was well tolerated, but combined with replacement of both vessels it was lethal because of outflow block and shock. Total liver blood flow should be kept as high as possible during such procedures in man.